Is it Effective using Peer Tutoring with Realistic Mathematics Education Approach to Improve Slow Learnersâ Mathematics Attitudes? - Putranto, Sumbaji; Marsigit, Marsigit (International Journal on Emerging Mathematics Education, 2018)
This study was aimed to describe the effectiveness of peer tutoring method with Realistic Mathematics Education approach applied in inclusive classes to improve slow learners mathematics attitudes. Type of this research was quasi experiment with one-group pretest-posttest design. The sample was chosen by using convenience sampling from slow learners of VII Grade Junior High School which consisted of 31 students scattered into 3 inclusive classes. The instrument used in this study was a non-test instrument in form of questionnaires. The effectiveness criteria in this study was based on 1) the average score of final questionnaire was higher than the initial questionnaire score, 2) the final questionnaire score shows that more than 75% of the whole students gained the minimum âgoodâ criteria. The result shows that applying peer tutoring learning method with Realistic Mathematics Education approach in inclusive classes was effective to improve slow learners mathematics attitudes.